Les maisons du Haut-Empire de la rue de l’Oratoire à Augustonemetum / Clermont-Ferrand (Puy-de-Dôme) - Julien Ollivier; Sabine Groetembril; Julie Massendari; Laëtitia Pédoussaut; Julie Viriot (Revue Archéologique du Centre de la France)
An archaeological excavation allowed to recognize in 2010 several states of a residential tenement portion near the monumental center of Augustonemetum/Clermont-Ferrand. Its evolution has been followed, as well as the street’s one which lines it in the North. The decumanus seems to be set up at the very beginning of the 1st century and the oldest domus, which present a rich decoration (mosaics, mural paintings), are built during the first half of the 1st century. They are destroyed in the hinge of 1st and 2nd centuries and replaced by new houses, after a redefining of the properties inside the insula, which seems abandoned in the course of the 3rd century. The site is reinvested only during the Late Middle Ages. In this time, antique constructions are systematically destroyed.